Noise reduction multi-layer material, preparation method thereof, noise reduction structure containing noise reduction multi-layer material and range hood
By laying a nanofiber membrane layer on the surface of the elastic porous material layer, the problem of poor noise reduction effect of the traditional noise reduction structure in medium and high frequencies under limited thickness is solved, and a wide-band noise reduction effect is achieved without affecting the flow resistance in the flow field environment.
Patent Information
- Application Number
- CN202411753856.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional noise reduction structures are difficult to achieve wide-band mid- and high-frequency noise reduction with limited thickness, and the increase in thickness in a flow field environment leads to increased flow resistance, affecting the noise reduction effect.
A composite structure of an elastic porous material layer and a nanofiber membrane layer is adopted. The thickness of the nanofiber membrane layer is less than 1mm. The adhesion effect drives the elastic porous material to vibrate and lose sound energy, thereby increasing the mid- and high-frequency sound absorption effect.
Without increasing the thickness of the structure, the mid- and high-frequency sound absorption coefficient is significantly improved, and the flow field is kept unobstructed, thereby improving the noise reduction effect.
Smart Images

Figure CN119541439A_ABST
Abstract
Description
Technical Field
[0001] The invention specifically relates to a noise reduction multilayer material and a preparation method thereof, a noise reduction structure and a range hood containing the same. Background Art
[0002] At present, traditional noise reduction structures mainly include micro-perforated plates, Helmholtz resonators and porous materials. Among them, the noise reduction mechanism of micro-perforated plates and Helmholtz resonators mainly comes from the loss caused by the local resonance of the neck and the air in the cavity to consume the incident sound energy, while the noise reduction mechanism of porous materials comes from the loss of sound energy caused by the viscosity effect of air when the sound wave propagates in the pores of porous materials.
[0003] Under the constraint of conventional thickness (3cm-5cm), the main noise reduction frequency band of the micro-perforated plate is in the mid-frequency band of 500Hz-1500Hz, and its low-frequency sound absorption mainly depends on the depth of the back cavity; although the Helmholtz resonator and its corresponding special-shaped Helmholtz sound-absorbing structure can achieve sound absorption below 500Hz, the efficient sound absorption frequency band is narrow, usually between a few Hz and tens of Hz, and it is difficult to break through 100Hz. Under the constraint of conventional thickness, the efficient sound absorption frequency band of porous materials is usually above 1000Hz. In order to achieve a broadband and strong loss effect, traditional noise reduction solutions often require a relatively thick structure, which not only increases the cost of the noise reduction structure, but also when applied to flow field noise reduction, the thicker structure will bring greater air intake resistance and noise, thereby making the noise reduction effect worse. In the case of limited thickness, these composite noise reduction lining structures often have limited noise reduction effects in the mid- and high-frequency range. Therefore, it is difficult for traditional noise reduction structures to achieve broadband and efficient sound absorption in a compact space, that is, the loss capacity of sound energy based on the local resonance mechanism or the viscosity and heat loss effect of air is limited. At the same time, in an environment where a flow field exists, the noise reduction lining structure composed of micro-perforated plates, porous materials and Helmholtz resonators formed based on the viscosity effect of air and the local resonance mechanism usually has an adverse effect on the flow field due to the increase in thickness, thereby reducing the noise reduction effect. How to significantly enhance the noise reduction performance of the noise reduction structure in the case where the effect on the flow field in the flow channel of the range hood is negligible is the main problem that needs to be solved in this field. Summary of the invention
[0004] The present invention is mainly to overcome the defects of the prior art in that a range hood has a flow channel, and simultaneously realizes broadband noise reduction in the medium and high frequencies without affecting the noise reduction effect in the flow field, and provides a noise reduction multilayer material and a preparation method thereof, a noise reduction structure containing the same, and a range hood. The noise reduction multilayer material provided by the present invention can significantly increase the medium and high frequency sound absorption coefficient of the composite superstructure while ensuring that the thickness of the structure remains basically unchanged, and after implementation, the noise reduction effect is improved without affecting the flow field.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions.
[0006] The present invention provides a noise reduction multilayer material, which comprises an elastic porous material layer and a nanofiber membrane layer arranged on at least one surface of the elastic porous material layer, wherein the thickness of the nanofiber membrane layer is less than 1 mm.
[0007] In the present invention, the elastic porous material layer may be an elastic framework porous material with a certain degree of deformability as commonly understood in the art, wherein the porous material refers to a material having a network structure composed of interconnected or closed pores.
[0008] In the present invention, the raw material of the elastic porous material layer can be one or two of polyurethane and polyester fibers conventionally used in the art.
[0009] In the present invention, the thickness of the elastic porous material layer can be 10mm-30mm, preferably 10mm-20mm. The elastic porous material layer mainly loses the sound energy entering the porous material through the thermal adhesion between the pores, so it has a good noise reduction effect on medium and high frequency noise. However, when the noise reduction space is limited, the thickness of the elastic porous material layer itself will be constrained, so that the medium and high frequency noise reduction effect will be significantly reduced.
[0010] In the present invention, the thickness ratio of the elastic porous material layer to the nanofiber membrane layer may be (20-300):1, for example, 300:1.
[0011] In the present invention, the fiber diameter in the nanofiber membrane layer may be 300nm-1000nm, for example, 500nm.
[0012] In the present invention, the density of the elastic porous material layer can be 15 kg / m 3 -20 kg / m 3 , for example 15 kg / m 3 .
[0013] In the present invention, the flow resistance of the elastic porous material layer can be 5000 Pa·s·m -3 -12000Pa·s·m -3 , for example 10000 Pa·s·m -3 .
[0014] In the present invention, the porosity of the elastic porous material layer may be 0.9-0.99, for example 0.95.
[0015] In the present invention, the tortuosity of the elastic porous material layer may be 1.04-1.1, such as 1.05 or 1.07.
[0016] In the present invention, the thermal characteristic length of the elastic porous material layer may be 400 μm-800 μm, for example, 672 μm.
[0017] In the present invention, the characteristic viscosity length of the elastic porous material layer may be 200 μm-400 μm, for example, 273 μm.
[0018] In the present invention, the material of the nanofiber membrane layer can be a polymer material commonly used in the art, such as any one of polyacrylonitrile, polyvinyl alcohol and polyvinyl pyrrolidone.
[0019] In the present invention, the thickness of the nanofiber membrane layer is preferably 0.1 mm-0.5 mm, such as 0.1 mm.
[0020] The present invention provides a method for preparing a noise reduction multilayer material, which comprises the following steps: applying a nanofiber membrane layer on at least one surface of an elastic porous material layer, wherein the thickness of the nanofiber membrane layer is less than 1 mm.
[0021] In some specific embodiments, the nanofiber membrane layer is only applied on one surface of the elastic porous material layer.
[0022] In the present invention, the laying method may be a conventional method in the art, and the purpose is to composite the nanofiber membrane layer with the elastic porous material layer. The laying method may be bonding or spraying. The bonding is preferably bonding the nanofiber membrane layer with the elastic porous material layer through a binder, and the binder is preferably HY-T160PP slow-drying glue. The spraying is preferably spraying the slurry for preparing the nanofiber membrane layer on the surface of the elastic porous material layer.
[0023] In the present invention, the nanofiber membrane layer may be a meltblown layer material.
[0024] In the present invention, the preparation method of the nanofiber membrane layer can be any one of a stretching method, a template synthesis method, a phase separation method, a self-assembly method and an electrostatic spinning method.
[0025] In some specific embodiments, the nanofiber membrane layer is prepared by electrospinning, which includes the following steps: dissolving a polymer in an organic solvent to prepare a spinning solution; and then spinning the spinning solution.
[0026] Wherein, the polymer is preferably any one of polyacrylonitrile, polyvinyl alcohol and polyvinyl pyrrolidone; the molecular weight of the polyacrylonitrile is preferably 50,000-200,000.
[0027] Wherein, the organic solvent is preferably DMF or DMAC.
[0028] The dissolution is preferably carried out under conditions of heating and stirring; the heating method is preferably water bath heating; the heating temperature is preferably 50-70°C, such as 60°C.
[0029] The dissolution time is preferably 2-6 hours, for example 4 hours, and the dissolution is performed until the solution is clear and transparent.
[0030] Wherein, in the spinning solution, the mass concentration of the polymer is preferably 5%-15%, for example 10%.
[0031] The receiving distance of the spinning is preferably 15-20 cm, such as 15 cm.
[0032] The liquid supply rate of the spinning is preferably 0.2-3 mL / h, such as 0.25 mL / h or 1 mL / h.
[0033] The power supply voltage for spinning is preferably: the positive voltage is in the range of 10-20 kV, and the negative voltage is 5 kV, for example, the positive voltage is 20 kV, and the negative voltage is 5 kV.
[0034] The spinning process parameters preferably also meet the following requirements: the specification of the injection pump is 20 mL, the roller speed is 300 rpm, the slide stroke is 20 cm, the temperature is 35° C., the humidity is 40%, and the timing is 120 min.
[0035] Wherein, the receiving substrate for spinning is preferably any one of aluminum foil, release paper, non-woven fabric, mesh cloth and the elastic porous material layer.
[0036] In the present invention, the fiber diameter in the nanofiber layer membrane may be 300nm-1000nm, for example, 500nm.
[0037] The present invention provides a noise reduction multilayer material, which is prepared by the preparation method as described above.
[0038] In the present invention, the shape of the noise reduction structure is preferably wedge-shaped.
[0039] The present invention provides a noise reduction structure, which comprises the noise reduction multi-layer material as described above.
[0040] The present invention provides a range hood, which comprises the noise reduction multilayer material or noise reduction structure as described above.
[0041] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0042] The reagents and raw materials used in the present invention are commercially available.
[0043] The positive and progressive effects of the present invention are:
[0044] The present invention achieves a significant increase in the mid- and high-frequency sound absorption effect while maintaining a comparable structure thickness by compounding the nanofiber membrane layer with the elastic porous material layer, and has no significant effect on the flow field and flow rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the SEM image of the elastic porous material layer in Example 1.
[0046] Figure 2 2 are SEM images of the nanofiber membrane layers in Examples 1 and 2.
[0047] Figure 3 Schematic diagram of the structure of the noise reduction multilayer material prepared in Example 1 and a SEM image of the interface (1-nanofiber membrane layer; 2-elastic porous material layer).
[0048] Figure 4 It is a curve diagram of the sound absorption coefficient of the noise reduction multilayer material in the embodiment and the comparative example.
[0049] Figure 5 Schematic diagram of the installation position of the noise reduction material in the range hood in Application Example 1 and Application Comparative Example 2 (1-nanofiber membrane layer; 2-elastic porous material layer; 3-centrifugal fan; 4-auxiliary air inlet cotton; 5-range hood; 6-airflow direction).
[0050] Figure 6 The three-view diagrams show the shapes of the noise reduction materials in Application Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0051] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0052] The sources of the raw materials in the embodiments of the present invention and the comparative examples are as follows:
[0053] Polyurethane elastic porous material was purchased from Anhui Meishijia New Materials Co., Ltd.
[0054] Polyacrylonitrile was purchased from Pandex (Shanghai) International Trading Co., Ltd.; the weight average molecular weight was 25,000.
[0055] Polyester fiber elastic porous material was purchased from Anhui Tingyou New Material Technology Co., Ltd.
[0056] The porous ceramic material was purchased from Zhengzhou Rongsheng Kiln Refractory Material Co., Ltd.
[0057] Example 1
[0058] A polyurethane elastic porous material with a thickness of 3 cm was used as the elastic porous material layer, and a nanofiber membrane layer with a thickness of 0.1 mm was sprayed on one surface of the polyurethane by electrospinning to obtain a noise reduction multilayer material.
[0059] Figure 1 This is the SEM image of the elastic porous material layer. Figure 2 This is the SEM image of the nanofiber membrane layer. Figure 3 Figure 3 is a schematic diagram of the structure of the noise reduction multilayer material and a microstructure diagram of the interface, where Figure a is a schematic diagram of the structure of the noise reduction multilayer material, and Figure b is a SEM image of the interface between the elastic porous material layer and the nanofiber membrane in the noise reduction multilayer material.
[0060] Among them, the density of the elastic porous material layer is 15kg / m 3 , flow resistance is 10000·Pa·s·m -3 , porosity is 0.95, tortuosity is 1.05; thermal characteristic length is 672μm; viscous characteristic length is 273μm.
[0061] Among them, the nanofiber diameter of the nanofiber membrane layer is 500nm;
[0062] Among them, the electrospinning process is:
[0063] (1) Preparation of spinning solution: Weigh a certain amount of polyacrylonitrile (PAN) and add it to DMF. Stir it with a magnetic stirrer at a water bath temperature of 60°C for 4 h until the solution becomes clear and transparent, thereby obtaining a PAN spinning solution with a mass concentration of 10%;
[0064] (2) Spinning: The PAN spinning solution is drawn into a 20 mL syringe, which is fixed to the syringe pump of the spinning machine. A 20G (1 / 2 inch, flat-mouth) stainless steel needle is installed. The needle is connected to the positive electrode of the high-voltage power supply, and the receiving roller is connected to the negative electrode of the high-voltage power supply. The polyurethane porous material is attached to the roller as a receiving substrate; the receiving distance is adjusted to 15 cm; the syringe pump specification is set to 20 mL, the liquid supply speed is 0.25 mL / h, the roller speed is 300 rpm, the slide stroke is 20 cm, the spinning voltage is: positive 20 kV, negative 5 kV, the temperature is 35 ° C, the humidity is 40%, the timing is 120 min, and finally the equipment door is closed and the exhaust is turned on. After the spinning is completed, the noise reduction multilayer material is obtained.
[0065] Example 2
[0066] A polyester fiber elastic porous material with a thickness of 3 cm was used as the elastic porous material layer, and a nanofiber membrane layer with a thickness of 0.1 mm was sprayed on one surface of the white polyester fiber porous material by electrospinning to obtain a noise reduction multilayer material.
[0067] Among them, the density of the elastic porous material layer is 15kg / m 3 , flow resistance is 10000 Pa·s·m -3 , tortuosity is 1.07, porosity is 0.95, thermal characteristic length is 672 μm, and viscous characteristic length is 273 μm;
[0068] The diameter of the nanofibers in the nanofiber membrane layer is between 300nm and 500nm;
[0069] Among them, the electrospinning process is:
[0070] (1) Preparation of spinning solution: Weigh a certain amount of polyacrylonitrile (PAN) and add it to DMF. Stir it with a magnetic stirrer at a water bath temperature of 60°C for 4 h until the solution becomes clear and transparent, thereby obtaining a PAN spinning solution with a mass concentration of 10%;
[0071] (2) Spinning: The PAN spinning solution is drawn into a 20 mL syringe, which is fixed to the spinning machine injection pump. A 20G (1 / 2 inch, flat-mouth) stainless steel needle is installed. The needle is connected to the positive electrode of the high-voltage power supply, and the receiving roller is connected to the negative electrode of the high-voltage power supply. The polyester fiber porous material is attached to the roller as a receiving substrate; the receiving distance is adjusted to 15 cm; the injection pump specification is set to 20 mL, the liquid supply speed is 0.25 mL / h, the roller speed is 300 rpm, the slide stroke is 20 cm, the spinning voltage is: positive 20 kV, negative 5 kV, the temperature is 35 ° C, the humidity is 40%, and the timing is 120 min. Finally, the equipment door is closed and the exhaust is turned on. After the spinning is completed, the noise reduction multilayer material is obtained.
[0072] Application Example 1
[0073] The noise reduction multilayer material prepared in Example 1 was cut into structural dimensions with a side length of 33 cm and wedge thicknesses of 14.5 mm and 38.5 mm, respectively, and installed in a range hood.
[0074] Among them, the elastic porous material layer in the noise reduction multilayer material and the inner wall of the main radiation noise are fixed with aluminum foil tape; the nanofiber membrane layer is made of multiple small samples with a length of 10 cm, a width of 5 cm, and a thickness of × 0.1 mm, which are spliced along the length or width on the same horizontal plane and further fixed with thin wires.
[0075] Comparative Example 1
[0076] A polyurethane elastic porous material with a thickness of 3 cm is used as the noise reduction material.
[0077] Comparative Example 2
[0078] A polyester fiber elastic porous material with a thickness of 3 cm is used as the noise reduction material.
[0079] Comparative Example 3
[0080] A porous ceramic material with a thickness of 3 cm is used as the noise reduction material.
[0081] Comparative Example 4
[0082] A porous ceramic material with a thickness of 3 cm was used as the porous material layer, and a nanofiber membrane layer with a thickness of 0.1 mm was sprayed on one surface of the ceramic porous material by electrospinning to obtain a noise reduction multilayer material.
[0083] Application Comparative Example 1
[0084] The bare range hood without any noise reduction material installed.
[0085] Application Comparative Example 2
[0086] A range hood equipped with the polyurethane elastic porous material of Comparative Example 1.
[0087] Effect Example 1 Sound Absorption Coefficient
[0088] A B&K impedance tube with an inner diameter of 29 mm was used, and the upper limit frequency of the test was 6400 Hz. The sound absorption coefficient of the composite structure of porous materials with different properties and electrospinning was tested based on the transfer function method. The effect data of the average sound absorption coefficient in the test frequency band are shown in Table 1 and Figure 4 As shown in (a)-(c) in the figure.
[0089] Table 1
[0090] Implementation Average sound absorption coefficient Example 1 0.7280 Example 2 0.7288 Comparative Example 1 0.4475 Comparative Example 2 0.4459 Comparative Example 3 0.7422 Comparative Example 4 0.7096
[0091] Figure 4 (a)-(c) are the sound absorption coefficient curves of the noise reduction multilayer materials of Examples 1-2 and Comparative Examples 1-4, respectively. Among them, Example 1 and Comparative Example 1 compare the average sound absorption coefficients of the polyurethane elastic porous material in the test frequency band before and after the composite electrospinning material, which are 0.4475 and 0.7280, respectively. By compounding the nanofiber membrane layer with a thickness of only 0.1 mm, the average sound absorption coefficient increased by 0.2805; Example 2 and Comparative Example 2 compare the average sound absorption coefficients of the polyester fiber elastic porous material in the test frequency band before and after the composite electrospinning material, which are 0.4459 and 0.7288, respectively, and the average sound absorption coefficient increased by 0.2829. This shows that no matter whether the frame of the porous material is hard or soft, as long as it has a certain elasticity, after the sound wave is incident, the multi-fluff fibers in the nanofiber membrane layer and the elastic frame vibrate together, which can significantly lose the incident sound energy and achieve a significant increase in the sound absorption coefficient.
[0092] When the porous ceramic material of the composite rigid frame of the nanofiber membrane structure was verified in Comparative Examples 3 and 4, since the multi-pile fibers of the nanofiber membrane could not drive the frame of the porous ceramic material to vibrate and lose sound energy, the average sound absorption coefficient of the porous ceramic material before and after the composite nanofiber membrane layer was 0.7422 and 0.7096 respectively, and the sound absorption coefficient decreased by 0.0326. This is because after the composite nanofiber membrane layer, the matching of the equivalent impedance of the nanofiber membrane layer and the air is lower than that of the porous ceramic material, so the sound energy entering the porous ceramic material is reduced, and the sound absorption coefficient becomes worse.
[0093] Effect Example 2 Noise Reduction Amount
[0094] The noise reduction materials in the embodiment and the comparative example are installed in the range hood. The three-view drawing of the shape of the noise reduction material is as follows: Figure 6 As shown, Figure 6 In the figure, (a) is the main view, (b) is the side view, and (c) is the top view (L1=14.5mm, L2=38.5mm, L3=330mm, L4=330mm). The noise test was completed in a semi-anechoic chamber environment. According to the noise level calculation method in the national standard GB / T17713-2011 "Appendix E of Range Hood: Noise Test Method", the noise reduction material without noise reduction material (application comparison example 1); the noise reduction material without nanofiber membrane layer (application comparison example 2); the noise reduction multilayer material of the present invention (application example 1) was installed. Under the same motor current conditions, the values of the A-weighted sound pressure level at the four test points under the three schemes are shown in Table 2.
[0095] Table 2
[0096] Implementation Test point 1 Test point 2 Test point 3 Test point 4 average value Application Example 1 50.4 dB(A) 52.7 dB(A) 55.3 dB(A) 51.7 dB(A) 52.525dB (A) Application Comparative Example 1 52.2 dB(A) 55.9 dB(A) 58.2 dB(A) 55 dB(A) 55.325 dB(A) Application Comparative Example 2 50.8 dB(A) 52.9 dB(A) 55.6 dB(A) 51.9 dB(A) 52.875 dB(A)
[0097] According to the data in Table 2, it can be seen that the laying of 0.1 mm nanofiber membrane in the present invention increases the noise reduction by 0.35 dB(A) compared with the noise reduction material without laying nanofiber membrane when the structural thickness remains unchanged. The final implementation effect proves that the improvement in noise reduction by compounding 0.1 mm nanofiber membrane is equivalent to the noise reduction effect brought by the increase in thickness of 10 mm-15 mm porous material in the current implementation effect, and will not cause negative changes in flow field and flow due to changes in thickness.
[0098] At the same time, in the implementation of range hood noise reduction, since the average thickness of the polyurethane elastic porous material is (14.5mm+38.5mm) / 2=26.5mm, which exceeds the optimal thickness of the noise reduction multi-layer material to improve the noise reduction (10-20mm, which can reduce 0.7dB year-on-year), the noise reduction amount is slightly smaller.
[0099] Through this invention, a method of laying a nanofiber membrane on the surface of a thinner elastic porous material layer is used. Since the nanofiber membrane laid on the surface of the elastic porous material layer has a certain adhesion effect, when noise sound waves are incident, the vibration of the material surface is driven to elastically couple the porous material to vibrate together, thereby effectively attenuating the sound energy, thereby achieving the same noise reduction as a thicker elastic porous noise reduction material, while making the flow channel of the range hood more unobstructed and thereby increasing the flow rate, which will bring more design flexibility to the structural design of the elastic porous material layer and the structural size of the range hood.
[0100] In addition, the noise reduction structure of the present invention is flow-field friendly, and its advantages are mainly reflected in: first, the wedge-shaped structure has a flow-guiding effect, which can reduce irregular small vortices in the flow channel; second, after laying the 0.1mm thick nanofiber membrane, the overall thickness of the structure remains almost unchanged, so there is almost no effect on the flow field; moreover, after laying the 0.1mm thick nanofiber membrane, the sound absorption coefficient of the composite structure can be increased, that is, the effect of the original thicker elastic porous material layer can be achieved while ensuring a thinner elastic porous material layer, which can widen the range hood air inlet flow channel, make the air inlet more unobstructed, or provide the possibility for a more compact range hood design.
[0101] The embodiments described above are only some embodiments of the present invention, which are convenient for those skilled in the art to understand and use the present invention. Obviously, any person skilled in the art can slightly modify or change the present embodiment and apply it to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and any equal changes, simple modifications and modifications made within the scope of the present invention still belong to the scope of the present invention.
Claims
1. A noise reduction multilayer material, characterized in that: The invention comprises an elastic porous material layer and a nanofiber membrane layer arranged on at least one surface of the elastic porous material layer, and the thickness of the nanofiber membrane layer is less than 1 mm.
2. The noise reduction multilayer material according to claim 1, characterized in that: The raw material of the elastic porous material layer is polyurethane and / or polyester fiber; And / or, the material of the nanofiber membrane layer is any one of polyacrylonitrile, polyvinyl alcohol and polyvinyl pyrrolidone; And / or, the thickness of the elastic porous material layer is 10 mm-30 mm, preferably 10 mm-20 mm; And / or, the thickness of the nanofiber membrane layer is 0.1 mm-0.5 mm, for example 0.1 mm; And / or, the fiber diameter in the nanofiber membrane layer is 300nm-1000nm, for example 500nm; And / or, the thickness ratio of the elastic porous material layer to the nanofiber membrane layer is (20-300):1, for example, 300:
1.
3. The noise reduction multi-layer material according to claim 1, characterized in that: The density of the elastic porous material layer is 15 kg / m 3 -20 kg / m 3 , for example 15kg / m 3 ; And / or, the flow resistance of the elastic porous material layer is 5000 Pa·s·m -3 -12000Pa·s·m -3 , for example 10000Pa·s·m -3 ; and / or, the porosity of the elastic porous material layer is 0.9-0.99, for example 0.95; and / or, the tortuosity of the elastic porous material layer is 1.04-1.1, for example, 1.05, 1.07; And / or, the thermal characteristic length of the elastic porous material layer is 400 μm-800 μm, for example, 672 μm; And / or, the elastic porous material layer has a viscosity characteristic length of 200 μm-400 μm, such as 273 μm.
4. A method for preparing a noise reduction multilayer material, characterized in that: The method comprises the following steps: laying a nanofiber membrane layer on at least one surface of an elastic porous material layer, wherein the thickness of the nanofiber membrane layer is less than 1 mm.
5. The method for preparing the noise reduction multilayer material according to claim 4, characterized in that: The nanofiber membrane layer is only applied on one surface of the elastic porous material layer; And / or, the laying method is bonding or spraying, preferably spraying; the bonding is preferably bonding the nanofiber membrane layer and the elastic porous material layer through a binder; the binder is preferably HY-T160PP slow-drying glue; the spraying is preferably spraying the slurry for preparing the nanofiber membrane layer on the surface of the elastic porous material layer; And / or, the nanofiber membrane layer is a melt-blown layer material; And / or, the fiber diameter in the nanofiber membrane layer is 300nm-1000nm, for example, 500nm.
6. The method for preparing the noise reduction multilayer material according to claim 5, characterized in that: The preparation method of the nanofiber membrane layer is any one of a stretching method, a template synthesis method, a phase separation method, a self-assembly method and an electrospinning method, preferably an electrospinning method; The electrostatic spinning method comprises the following steps: dissolving a polymer in an organic solvent to obtain a spinning solution; and spinning the spinning solution.
7. The method for preparing the noise reduction multilayer material according to claim 6, characterized in that: The electrospinning method satisfies one or more of the following conditions ①-⑨: ① The polymer is any one of polyacrylonitrile, polyvinyl alcohol and polyvinyl pyrrolidone; the molecular weight of the polyacrylonitrile is preferably 50,000-200,000; ② The organic solvent is DMF or DMAC; ③ The dissolution is carried out under heating and stirring conditions; the heating method is preferably water bath heating; the heating temperature is preferably 50-70°C, for example 60°C; ④ The dissolution time is 2-6h, for example 4h; ⑤ In the spinning solution, the mass concentration of the polymer is 5%-15%, for example 10%; ⑥ The receiving distance of the spinning is 15-20 cm, for example 15 cm; ⑦ The liquid supply rate of the spinning is 0.2-3 mL / h, for example 0.25 mL / h or 1 mL / h; ⑧ The power supply voltage for spinning is: the positive voltage ranges from 10-20 kV, and the negative voltage is 5 kV, for example, the positive voltage is 20 kV, and the negative voltage is 5 kV; ⑨ The receiving substrate for spinning is any one of aluminum foil, release paper, non-woven fabric, screen cloth and the elastic porous material layer.
8. A noise reduction multilayer material, characterized in that: It is prepared by the preparation method described in any one of claims 4 to 7.
9. A noise reduction structure, characterized in that: It comprises the noise reduction multi-layer material according to any one of claims 1 to 3 and 8, and the shape of the noise reduction structure is preferably wedge-shaped.
10. A range hood, characterized in that: It comprises the noise reduction multi-layer material according to any one of claims 1 to 3 and 8 or the noise reduction structure according to claim 9.
Citation Information
Patent Citations
Noise reduction assembly for range hood and range hood
CN114811682A
Preparation method of noise reduction material for range hood
CN117841433A
Micro-nano gradient fiber and film acoustic metamaterial composite structure
CN118560121A
Sound absorbing material and method of manufacturing sound absorbing material
JP2022185471A
Sheet metal bending machine
KR102650529B1